A17 EFFICACY AND SAFETY OF FILGOTINIB AS MAINTENANCE THERAPY FOR PATIENTS WITH MODERATELY TO SEVERELY ACTIVE ULCERATIVE COLITIS: RESULTS FROM THE PHASE 2B/3 SELECTION STUDY. (4th March 2021) - Peyrin-Biroulet, L; Loftus, E V; Danese, S; Vermeire, S; Sandborn, W J; Fogel, R; Nijhawan, S; Kempinski, R; Filip, R; Hospodarskyy, I; McNally, J; Yun, C; et al.
Abstract: Aims: SELECTION (NCT02914522) Maintenance evaluated filgotinib (FIL), a preferential JAK1 inhibitor, as maintenance therapy for patients (pts) with moderately to severely active ulcerative colitis (UC) who achieved clinical remission or Mayo Clinic Score (MCS) response after 10 weeks of FIL 200mg QD, FIL 100mg QD or placebo (PBO) induction. Methods: Pts randomized to FIL induction were rerandomized 2:1 to their induction FIL dose or PBO; pts randomized to PBO induction continued PBO maintenance. Steroid tapering was mandatory. The primary endpoint was clinical remission at Week 58. Key secondary endpoints and exploratory endpoints were assessed at Week 58. Results: 664 pts were treated in the Maintenance Study (n=93, 270, and 301 from induction with PBO, FIL 100mg and FIL 200mg); efficacy analyses included only FIL induction pts. Baseline demographics and disease characteristics were generally balanced across treatment arms; 40% were biologic experienced. Significantly higher proportion of pts on FIL 200mg or FIL 100mg were in clinical remission vs PBO. Significantly higher proportions of pts achieved key secondary endpoints with FIL 200mg vs PBO. More pts on FIL 200 mg or FIL 100mg achieved an MCS response and endoscopic improvement vs PBO. Incidences of adverse events (AEs), serious AEs and discontinuations due to AEs were similar across arms. Serious infection (<2%) and herpes zoster (<1%) were infrequent among FIL-treated patients. There were no venous thromboses, including pulmonary embolism, among FIL-treated pts. Two pts on FIL 200mg died, both AEs leading to death were considered unrelated to FIL. Conclusions: FIL 200mg and FIL 100mg were effective as maintenance treatment for pts with moderately to severely active UC who had achieved clinical response to FIL induction treatment. FIL 200 mg met all key secondary endpoints including endoscopic, histologic and 6-month corticosteroid-free remission. FIL was well tolerated in pts with moderate to severely active UC. Funding Agencies: None